Selective catalytic reduction of NO with NH3 over Mo–Fe/beta catalysts: the effect of Mo loading amounts. Issue 12 (23rd January 2017) - Deng, Jianlin; Liu, Jixing; Song, Weiyu; Zhao, Zhen; Zhao, Liang; Zheng, Huiling; Lee, Alex Chinghuan; Chen, Yongsheng; Liu, Jian
Abstract : The addition of Mo showed a promoting effect on the activity of Fe/beta for NH3 -SCR in a wide temperature range. Abstract : A series of Mo x –Fe/beta catalysts with constant Fe and variable Mo content were synthesized and investigated for selective catalytic reduction (SCR) of NO x with NH3 . It was found that the Mo0.2 –Fe/beta catalyst exhibited excellent activity, N2 selectivity and preferable resistance to H2 O and SO2 . The Mo x –Fe/beta catalysts were characterized by various analytical techniques. TEM and SEM images showed that the addition of Mo could enhance the dispersion of iron oxides. The results of NH3 -TPD and Py-IR indicated that the introduction of Mo resulted in a change of Brønsted acidity, which was associated with high-temperature SCR activity. XPS and XANES results showed that the introduction of Mo resulted in a change of Fe 2+ content, which determined the low-temperature activity. DFT calculations showed the strong effects of Mo on the crystal structure, charge distribution and oxygen vacancy formation energy of iron oxides, which further explained the role of Mo in the catalyst behaviors during the SCR process.